Familiar health expenditures of haemodialysis treatment in Tuxtla Gutierrez, Chiapas, for open and health-affiliated populations - Arce Moguel, Francisco Emmanuel (2018)
Objective: To identify the costs incurred by hemodialysis patients under different health coverage schemes in the city of Tuxtla Gutiérrez, in the context of a highly marginalized entity such as the state of Chiapas, Mexico. During the months of August-September 2017. Methods: Ethnographic, observational, descriptive study based on an intentional non-probabilistic sample of 21 cases addressed through individual interviews. The selection criteria were Chronic kidney disease etiology, sex, time spent on hemodialysis, treatment financing scheme, place of residence, and age. Results: Four modalities of treatment financing were identified.  Considering expenses for medication, transportation, travel expenses, medical consultations, laboratory studies, diet and hemodialysis. The group that reports the lower spending is institutional patients with an average of 308.94 USD per month, followed by surrogate patients who spend an average of $337.94 USD per month. Semi-private patients invest $768.89 USD each month and the group with the highest spending is private patients who spend an average of $1,530.61 USD monthly. Conclusions: The treatment of chronic kidney disease through hemodialysis has a monthly cost per patient that ranges from $308.9 USD to $1,530.61 USD, therefore, the chances that a household can assume the costs of treatment are based on the social security system they have access to, the physical and financial capital they have and the support networks they build.